Voices of Resistance from Africa: Analysis of “Huwa Summu” and “Sa’anhadlu” - Hasaniyah, Nur; 'Aidin, Tusamma Salsa Bila; Hasanah, Ummi; Mohammed, Fares Albadr (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
African literature reflects the continent’s rich tapestry of ethnic groups, languages, and cultures while offering complex perspectives on social realities including war, oppression, and discrimination. Literary sociology provides a valuable framework for comparative studies, revealing how different works represent these pressing social issues. This study examines how the poems “Huwa Summu” by Afnan Samir and the poem “Sa’anhadlu” by Noémia de Sousa represent both objective and subjective forms of social reality. The article explores and compares the social realities depicted in these two African poets’ works. Using a qualitative approach, the study draws on primary data from internet sources and secondary data from relevant journals and books. Data collection involved library research employing three primary techniques: reading, translation, and note-taking. The findings reveal that Afnan Samir’s “Huwa Summu” portrays objective social realities of oppression and religious themes while expressing subjective realities of sadness, confusion, lamentation, weakness, and disappointment. Noémia de Sousa’s “Sa’anhadlu” presents a contrasting, more optimistic perspective that emphasizes resistance, courage, and self-confidence despite addressing colonial oppression. This study contributes to scholarship through its comparative analysis of two Arabic-language African poems from different geographical, historical, and gender perspectives—an approach rarely explored in Indonesian literary studies. Future research should adopt an interdisciplinary approach, including deeper exploration of local political, cultural, and historical contexts.